2019
DOI: 10.1007/s00704-019-02908-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of frequent tropical cyclone activities over the western North Pacific and hot summer days in central-eastern China

Abstract: Tropical cyclones (TCs) formed over the western North Pacific (WNP) often make landfalls over East Asia and Southeast Asia, causing strong winds and torrential rain in the coastal countries. However, they also bring cool weather on hot summer days and mitigate drought impacts. The present study demonstrates that TC activities over the WNP can strongly modulate extreme summer weather events in eastern mainland China, i.e., frequent TC activities would indirectly lead to more hot days in central-eastern China al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The circulation patterns are similar to the circulations related to tropical cyclones (known as typhoons in the western North Pacific) because previous studies have suggested some potential connections between tropical cyclones and heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019). During the days with compound extremes, tropical cyclones are located close to or inside the study region (Figure 4), in agree with previous studies showing that tropical cyclones may be associated with heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019). During 1979-2019, we identify 157 days of compound extremes, 85 of which are accompanied by typhoons located west of 130 • E. Therefore, 54% of compound extremes coincide with typhoon activities, indicating an association between the compound extreme and typhoons.…”
Section: Analysis Results and Interpretationsupporting
confidence: 57%
See 1 more Smart Citation
“…The circulation patterns are similar to the circulations related to tropical cyclones (known as typhoons in the western North Pacific) because previous studies have suggested some potential connections between tropical cyclones and heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019). During the days with compound extremes, tropical cyclones are located close to or inside the study region (Figure 4), in agree with previous studies showing that tropical cyclones may be associated with heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019). During 1979-2019, we identify 157 days of compound extremes, 85 of which are accompanied by typhoons located west of 130 • E. Therefore, 54% of compound extremes coincide with typhoon activities, indicating an association between the compound extreme and typhoons.…”
Section: Analysis Results and Interpretationsupporting
confidence: 57%
“…The easterly winds along the north flank of the cyclonic system (Figure 3) can transport water vapor from the Pacific Ocean to the continent and may also contribute to the precipitation over Yangtze River (Yu et al, 2020). The circulation patterns are similar to the circulations related to tropical cyclones (known as typhoons in the western North Pacific) because previous studies have suggested some potential connections between tropical cyclones and heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019). During the days with compound extremes, tropical cyclones are located close to or inside the study region (Figure 4), in agree with previous studies showing that tropical cyclones may be associated with heat waves (Parker et al, 2013;Lin, 2019;Matthews et al, 2019;Zhong et al, 2019).…”
Section: Analysis Results and Interpretationmentioning
confidence: 76%
“…They also projected that a highly destructive sequence will result in the event of the successive effects of TCs and heat wave. Zhong et al (2019) discovered through an analysis of TCs in the western North Paci c (WNP) and hot summer days in central eastern China that when TCs occurred more frequently, there were more hot days in the central eastern China. They insisted that this is a feedback effect between TC for western North Paci c subtropical high (WNPSH), which governs a wide area from central eastern China to the Paci c Ocean of eastern Japan, and hot summer days in central eastern…”
Section: Introductionmentioning
confidence: 99%
“…Tropical cyclone (TC) is one of the most hazardous natural phenomena on Earth, which causes huge damage to human life and property for billions of people [1,2]. As one of the most active regions for TCs, the western North Pacific (WNP) basin experiences about 1/3 of the global TCs every year, which reach on average about 26 TCs annually [3].…”
Section: Introductionmentioning
confidence: 99%